2020
DOI: 10.3389/fneur.2020.00782
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: A Case of Severe Clinical Deterioration in a Patient With Multiple Sclerosis

Abstract: Tumefactive multiple sclerosis (MS) is a rare variant of MS that may lead to a rapidly progressive clinical deterioration requiring a multidisciplinary diagnostic workup. Our report describes the diagnostic and therapeutic approach of a rare and extremely severe course of MS. A 51-year-old man with an 8-year history of relapsing-remitting MS (RRMS) was admitted with a subacute progressive left lower limb weakness and deterioration of walking ability. After extensive investigations including repeated MRI, micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…This might lead to dysregulation of B-cell and plasma cell immune responses by altering the immunoregulatory T-cell phenotype. Occasional reports have identified IgG and complement deposition in TDLs (42)(43)(44)) and a number of reports citing the therapeutic effects of plasma exchange and rituximab imply B-cell and IgG-mediated mechanisms are also important (17,27,40,41). Proven antibody mediated diseases such as NMO-SD are associated with TDLs (4).…”
Section: Discussionmentioning
confidence: 99%
“…This might lead to dysregulation of B-cell and plasma cell immune responses by altering the immunoregulatory T-cell phenotype. Occasional reports have identified IgG and complement deposition in TDLs (42)(43)(44)) and a number of reports citing the therapeutic effects of plasma exchange and rituximab imply B-cell and IgG-mediated mechanisms are also important (17,27,40,41). Proven antibody mediated diseases such as NMO-SD are associated with TDLs (4).…”
Section: Discussionmentioning
confidence: 99%
“…Low-grade astrocytoma was the most frequent misdiagnosis in 39% of cases, followed by high-grade astrocytoma [ 5 ]. A study reported that differentiating tumefactive multiple sclerosis and intracerebral lymphoma is difficult in immunocompromised patients, thus brain biopsy should be considered [ 10 ]. The literature has described different cases of TMS that have been diagnosed without brain biopsy depending only on radiological and CSF results; however, in some cases, brain biopsy was an essential procedure to confirm the diagnosis and avoid mismanagement [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…In all three well-described cases, the predominant perivascular T cell subtype was CD8 cytotoxic T cells, whereas B cells were few. Creutzfeldt cells have been described in one case ( 93 ), and in another case deposits of complement and immunoglobulins were identified in the lesion as an antibody/complement mediated type of MS, described previously as MS pattern II ( 95 ). An interested case presented by Hashimoto et al ( 97 ) showed the reappearance of a TDL shortly after fingolimod initiation in a woman with a past history of a demyelinating disease beginning with isolated TDL, converted to classical relapsing remitting MS and subsequent new TDL emergence after fingolimod (no biopsy available) ( 97 ).…”
Section: Tumefactive Demyelinated Lesions–immunopathologymentioning
confidence: 92%
“…A rebound syndrome can occur as an increase in disease activity after treatment cessation in MS, especially in case of natalizumab or fingolimod. Cases with biopsy-proven TDL development have been described in MS patients under fingolimod treatment (93)(94)(95)(96). In all three well-described cases, the predominant perivascular T cell subtype was CD8 cytotoxic T cells, whereas B cells were few.…”
Section: Pathology Of Drug Induced Tdlsmentioning
confidence: 97%